COORDINATION EYS-FOOT AND THEIR RELATIONSHIP OF ACCURACY PERFORMANCE OF OFFENSIVE SKILLS FOR HANDBALL PLAYER AGE (13-14) - Khamees, Ahmed; Hasson, Murtada (Journal of Physical Education, 2015)
The study aimed to: identify the relationship between the coordination eys-foot and performance of offensive skills for handball player age (13-14) The hypothesis of the study: there is a significant correlation statistically significant differences between coordination and performance of offensive skills handball for ages (13-14), and the researcher used descriptive method connectivity relations، and the study sample includes 20 players from the reconstruction of (13-14) years، it was assisted by a researcher with a number of methods and tools in order to get (spss (which results were processed using program. The main conclusions are: there is a significant correlation between the coordination and dribbling skill, and there is a significant correlation between the coordination and skill handling and receiving relationship. The most important recommendations were: the need to devote time at the beginning of training unites for the training of coordination to their importance in the basic handball skills, and conducting regular tests to coordination to see the general level of players.